2008
DOI: 10.1111/j.1600-079x.2008.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

MT3/QR2 melatonin binding site does not use melatonin as a substrate or a co‐substrate

Abstract: Quinone reductase 2 (QR2, E.C. 1.10.99.2) is implicated in cell reactive oxygen species production. The catalytic activity of this enzyme is inhibited by 1 microM of melatonin. QR2 was identified as the third melatonin binding site (MT3). It is of major importance to understand the exact roles of melatonin and QR2 in oxidative stress. A fascinating possibility that melatonin could serve as a co-substrate or substrate of QR2 was hypothesized recently. In the current investigation, nuclear magnetic resonance stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 41 publications
(61 reference statements)
4
26
0
Order By: Relevance
“…These effects could be related to the activation of melatonin membrane receptors by AFMK, because luzindole (antagonist of these receptors) reversed AFMK-induced stimulation of HSPs in PANC-1 cells [94]. The observation concerning the involvement of MT 1 /MT 2 receptor in the effect of AFMK is in agreement with previous reports, showing that AFMK is able to bind to the melatonin membrane receptor, but its affinity to this receptor is lower than that of melatonin [34,95,96,97,98,99]. …”
Section: Melatonin System and Pancreatic Cancersupporting
confidence: 90%
“…These effects could be related to the activation of melatonin membrane receptors by AFMK, because luzindole (antagonist of these receptors) reversed AFMK-induced stimulation of HSPs in PANC-1 cells [94]. The observation concerning the involvement of MT 1 /MT 2 receptor in the effect of AFMK is in agreement with previous reports, showing that AFMK is able to bind to the melatonin membrane receptor, but its affinity to this receptor is lower than that of melatonin [34,95,96,97,98,99]. …”
Section: Melatonin System and Pancreatic Cancersupporting
confidence: 90%
“…They differ in affinity for their natural ligand, melatonin. To date, the MT3 receptor has been found in the liver, kidney, brain, oocyte and ovary [167e169] and is seemingly identical to the cystosolic enzyme, quinone reductase 2 (QR2) [170]. Melatonin exerts its action by generating a variety of different second messenger after its binding to membrane receptors depending on the specific cell and on the species.…”
Section: Melatonin: Receptors and Signal Transductionmentioning
confidence: 99%
“…Melatonin 3 type (MT-3) receptor has higher affinity to NAS than to melatonin, and was identified as the same protein as quinonereductase 2 (QR2) detoxifying and antioxidant enzyme [47]. We found that QR2/MT3 agonist 5-methoxycarbonylamino- N -acetyltryptamine (5MCA-NAT) decreased, while the QR2/MT3 antagonist prazosin increased the duration of immobility in the tail suspension test in C57BL/6 mice.…”
Section: Brecent Developmentsmentioning
confidence: 99%